2015
DOI: 10.1017/s0373463315000740
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Real-Time Regional Ionospheric Model Using IGS Real-Time Service (IGS-RTS) Products

Abstract: Recently, the International Global Navigation Satellite System (GNSS) Service (IGS) has launched the Real-Time Service (IGS-RTS). The RTS products enable real-time precise positioning applications. For single-frequency Real-Time Precise Point Positioning (RT-PPP), ionospheric delay mitigation is a major challenge. To overcome this challenge, we developed a Real-Time Regional Ionospheric Model (RT-RIM) over Europe using the RTS satellite orbits and clock products. The model has spatial and temporal resolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It should be also noted that the type of mapping function in the atmospheric effect calculation process contributes to the final solution accuracy as well. Allain and Mitchell (2009) examined the tomographic mapping function known as the Multi-Instrument Data Analysis System (MIDAS) with ionospheric effect determination for the single-frequency data. Research has shown that daily positioning errors are up to 50 % lower in comparison to positioning using the Klobuchar algorithm or IRI when the surrounding distribution of receivers are favourable.…”
Section: Spp With Ionospheric Corrections Using the Klobuchar Algoritmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be also noted that the type of mapping function in the atmospheric effect calculation process contributes to the final solution accuracy as well. Allain and Mitchell (2009) examined the tomographic mapping function known as the Multi-Instrument Data Analysis System (MIDAS) with ionospheric effect determination for the single-frequency data. Research has shown that daily positioning errors are up to 50 % lower in comparison to positioning using the Klobuchar algorithm or IRI when the surrounding distribution of receivers are favourable.…”
Section: Spp With Ionospheric Corrections Using the Klobuchar Algoritmentioning
confidence: 99%
“…High-quality representation of the ionosphere influence on positioning can be obtained by the global ionospheric models (GIMs), used mostly in the post-processing purposes as explained in Ciećko and Grunwald (2020). It is worth noting that Abdelazeem et al (2016) developed the regional ionospheric model over the European area and implemented it in precise point positioning (PPP), operating in real time using the real-time service (RTS) products of the IGS. The results present an improvement in the accuracy on the level of 40 % (under the midlatitude region) in the 3-D position relating to the IGS-GIM.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the International GNSS Service (IGS) RTS has been providing access to continuous real-time GNSS forecast ephemeris and clock corrections since the 1 April 2013 [ 28 , 29 ]. The accuracy of RTS products is about 8 cm for GPS ephemeris and 0.3 ns for GPS satellite clocks [ 28 , 30 ], which is enough high for real-time precise positioning.…”
Section: Time-relative Positioning Algorithm Based On Tdcp Measurementioning
confidence: 99%
“…The accuracy of the developed RIM is validated for PPP applications. It is found that the positioning accuracy of the proposed RIM is superior to that of the IGS-GIM, where the RMSE values are reduced from ±0·325 to 0·25 m and from ±0·904 to 0·499 m, for the horizontal and height components, respectively (Abdelazeem et al, 2015). In order to produce the RIM, GPS observations from a regional network consisting of 60 International GNSS Service (IGS) and EUREF reference stations are processed in the Bernese-5·20 PPP module in order to estimate the VTEC values.…”
Section: Introductionmentioning
confidence: 99%